2019
DOI: 10.1177/2150135118813124
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Post Fallot Repair Junctional Ectopic Tachycardia (JET)

Abstract: Background: Junctional ectopic tachycardia (JET) is a common arrhythmia causing hemodynamic impairment following corrective cardiac surgery such as tetralogy of Fallot (TOF) repair. Methods: We report our experience with postoperative JET following surgical repair of TOF. The retrospective study was done from 2003 to 2012 with a total of 105 patients who underwent TOF repair. These patients' clinical and electrocardiographic data (pre-, intra-, and postoperative) were monitored to identify risk factors for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…1,2,20 The risk factors associated with an increased incidence include the age of infant less than 6 months, the postoperative use of dopamine or milrinone, the use of prolonged aortic cross-clamp and cardiopulmonary bypass, and total surgical time. [1][2][3]8,38 The use of nitroprusside was associated with a reduced incidence of JET. 8 The type of cardiac surgery is also a factor, especially those that involve the crux of the heart including tetralogy of Fallot, AV canal, and ventricular septal defect repair, as well as repair of anomalous pulmonary venous return, arterial switch operation, Norwood procedure, and interrupted aortic arch repair.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,20 The risk factors associated with an increased incidence include the age of infant less than 6 months, the postoperative use of dopamine or milrinone, the use of prolonged aortic cross-clamp and cardiopulmonary bypass, and total surgical time. [1][2][3]8,38 The use of nitroprusside was associated with a reduced incidence of JET. 8 The type of cardiac surgery is also a factor, especially those that involve the crux of the heart including tetralogy of Fallot, AV canal, and ventricular septal defect repair, as well as repair of anomalous pulmonary venous return, arterial switch operation, Norwood procedure, and interrupted aortic arch repair.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…8 The type of cardiac surgery is also a factor, especially those that involve the crux of the heart including tetralogy of Fallot, AV canal, and ventricular septal defect repair, as well as repair of anomalous pulmonary venous return, arterial switch operation, Norwood procedure, and interrupted aortic arch repair. 1,20,38 Other risk factors associated are postoperative higher core temperature and imbalances of electrolytes. [39][40][41][42] Of note, all arrhythmias, including JET, are common in those with complex congenital heart disease especially the heterotaxy syndromes but the difficulty in the risk association is that most of these infants have had early surgical interventions.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…Left anterior descending artery (LAD) crossed RVOT in 14 (1.79%) of TAP/TV cases and to save LAD in all these cases, right ventricle to pulmonary artery (RV-PA) conduit (Contegra, Medtronic) of 16-20 mm size was implanted, while in TA/TP cases it was not needed (p=0.044). Others report similarly 15 .…”
Section: Discussionmentioning
confidence: 93%
“…This contrasts from reported rates of 19% to 37% of arrhythmia after early complete repair, with the majority having JET, leading to longer mechanical ventilation and intensive care unit stay. 3,11,[24][25][26][27] Bailey et al reported a lower incidence of postoperative arrhythmias in neonates after staged repair when compared to early complete repair (3.6% vs 19%, P ¼ .04). 11 Staged repairs may have lower rates of postoperative arrhythmias, as they may allow for older age, greater weight, and shorter bypass duration at complete repair, potentially improving these variables associated with postoperative arrhythmia.…”
Section: Commentmentioning
confidence: 99%